A percepção pública da ciência na comunicação das mudanças climáticas: caso de estudo de jornais online - Moutinho, Maria Elisa Pospissil (2023)
Climate change represents a global challenge, impacting both the present and the future of humanity. The way a phenomenon is addressed is crucially shaped by public perception. A key challenge in combating the climate emergency is how to communicate and motivate society to take urgent action, and the media are crucial to the public’s understanding of this problem. The aim of the research is to characterize the public perception of science in climate change communication. The methodological path to achieving this goal involves a bibliographical survey and content analysis of publications and readers’ comments in articles on climate change published in the online newspapers Gazeta do Povo and Folha de São Paulo, between January 2022 and June 2023. We analyzed 37 published articles and 2,492 comments from the sources cited. The main result is that, from the perspective of climate change communication – predominantly carried out by journalists who, using digital platforms, seek to bring information to citizens (readers) só that they can understand the phenomenon – the conclusion is that science is perceived by citizens, who are largely uninformed or misinformed, as something political and something to be treated with irony and skepticism. The results achieved can be useful in developing targeted campaigns that address precisely those areas where knowledge gaps or misinformation are widespread in order to educate the public about scientific issues such as climate change.